Penerapan Metode MOORA pada Sistem Pendukung Keputusan Pemilihan Kepala Laboran - Harianto, Kusno; Arfyanti, Ita; Yusika, Andi (Forum Kerjasama Pendidikan Tinggi, 2022)
In the process of carrying out academic activities in every university, it is inseparable from the existence of tendik. In college, the head of the laboratory is in charge of ensuring the implementation of the use of the laboratory in supporting the ongoing learning process. The head of the laboratory is in charge of regulating work mechanisms and procedures in the laboratory unit. The importance of the role of the head of laboratory for tertiary institutions requires universities to have a head of laboratory in accordance with the implementation of the tasks and responsibilities given. The selection of the head of the laboratory is not only done based on the length of work at the tertiary institution, but also must be seen from the knowledge, abilities, expertise, decision making and competency certificates possessed. Therefore, we need a way to help solve problems, especially by using a computerized system. Decision support system is a computerized information system. Decision support systems are widely used for corporate organizations to solve problems in the process of making or supporting decisions. The results obtained from the application of the MOORA Method are that alternative A1 was chosen to be the head of the laboratory with a final score of 0.48